?TERPENOIDS AND STEROIDS OF THE AERIAL PARTS OF MIRA BILlS JALAPA LINN. - SIDDIQUI, B.S.; ADIL, Q.; BEGUM, S. (Biological Sciences - PJSIR, 1994)
Three compounds including a diterpene, trans-phytol, apentacyclic triterpenoid, methyI3-oxo-urs-12-en-28-oate and a steroid, P-sitosterol acetate have been isolated for the first time from the fresh aerial parts of Mirabilis jalapa Linn. alongwith oleanolic acid, ursolic acid, p··sitosterol, brasicasterol and stigmasterol. Their structures have been established with the helpof spectral data. This is the first reportof2D NMR studies (Hetero-COSY, COSY -45, NOESY, Lresolvcd) of trans-phytol.